Chinese adults’ learning Thai as a foreign language in informal contexts / Wang Dong Hui Zi - Wang, Dong Hui Zi (2014)
The objectives of this thesis are 1) to illustrate the influence of cross-linguistic similarities in multilingual acquisition and 2) to investigate the problems and limitations with informal third language (L3) acquisition, focusing on young adult Mandarin speakers whose L1 is Mandarin and L2 is English and who acquire oral Thai as their L3 through informal learning in social interactions. The participants were Mandarin teachers who have acquired certain levels of Thai language while working in Thailand. In my study, I suggest that as both Thai and Mandarin are tonal languages that have similar sentence patterns, it is relatively easy for Mandarin speakers to acquire Thai. Using a survey and language proficiency tests, it is found that language distance affects the cross-linguistic influence in multi-linguals’ language acquisition. More specifically, when learners have knowledge of related languages that belong to the same language family (in this case, Sino-Tibetan), the background language (BL: Mandarin) that is closest to the target language (TL: Thai) will be a positive source for TL learning. In other words, cross-linguistic similarities can help learners to achieve the TL.